Analysis of Chemical Constituents Changing in Physical Process and Nutritional Components of Malus halliana Koehne Tea - Zhenhua Yin; Yong Zhang; Juanjuan Zhang; Wenyi Kang (Journal of Food Quality)
This study aimed to establish a HPLC method for simultaneous determination of the changing of quercitrin, 3-hydroxyphloridzin, and phloridzin in physical process of M. halliana tea. Meanwhile, the nutritional compositions were determined, using anthrone-sulfuric acid colorimetry and direct titration determination of total sugar and reducing sugar, respectively, in order to provide theoretical basis for quality control and tea production. The results showed that the regression equations for quercitrin, 3-hydroxyphloridzin, and phloridzin were linear in the range of 0.0972–12.15 μg (r=0.999 8), 0.0932~11.65 μg (r=0.999 1), and 0.9~112.5 μg (r=0.999 6), respectively. The average recoveries ranged from 98.19% to 99.35%. The contents of crude protein and the crude fat were measured by spectrophotometric detection and soxhlet extraction detection, respectively. The contents of total sugar, reducing sugar, the fat, and protein were 6.8 g/100 g, 8.5 mg/100 g, 2.399 g/100 g, and 4.362 g/100 g, respectively, in M. halliana tea.